Worldwide Assessment of Low- and Middle-Income Countries' Regulatory Preparedness to Approve Medical Products During Public Health Emergencies - Khadem Broojerdi, Alireza; Alfonso, Claudia; Ostad Ali Dehaghi, Razieh; Refaat, Mohamed; Sillo, Hiiti Baran (Frontiers in Medicine, 2021)
ABSTRACT Background. Regulatory preparedness for public health emergencies is critical. However, responses to past emergencies, such as the 2009 H1N1 influenza pandemic and medical product shortages, have revealed sizable gaps in countries’ regulatory capacity and preparedness. A systematic analysis of the regulatory preparedness of countries around the world has not yet been performed. Methods. From 2016–2020, we used the World Health Organization (WHO)’s Global Benchmarking Tool (GBT), a standardized instrument for identifying national regulatory authorities’ strengths and gaps, to analyze the regulatory preparedness of 84 Member States, 95% of which were low- or middle-income countries. We analyzed whether participating Member States had not implemented, displayed ongoing implementation, had partially implemented, or had fully implemented ten of the GBT’s 268 sub-indicators most relevant to regulatory preparedness for public health emergencies. Findings. Only ten Member States (12%) that underwent benchmarking had fully implemented all ten sub-indicators related to regulatory preparedness for public health emergencies; 34 (40%) had fully implemented ≥50% of the emergency sub-indicators, and 20 (24%) had not fully implemented any of the sub-indicators. With regard to individual sub-indicators, regulatory preparedness ranged from 19 Member States (23%) fully implementing reliance on clinical trial decisions of others to 45 (59%) fully implementing legal provisions to fast-track (or expedite) marketing authorization applications. Interpretation. Many WHO Member States have limited regulatory preparedness for a public health emergency. Strengthening regulatory systems and promoting Good Regulatory Practices and reliance in these countries, to enable efficient response to emergencies, should be a global health priority.